2020
DOI: 10.1038/s41598-020-60747-3
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening to Predict Chemical-Assay Interference

Abstract: The U.S. federal consortium on toxicology in the 21 st century (Tox21) produces quantitative, highthroughput screening (HTS) data on thousands of chemicals across a wide range of assays covering critical biological targets and cellular pathways. Many of these assays, and those used in other in vitro screening programs, rely on luciferase and fluorescence-based readouts that can be susceptible to signal interference by certain chemical structures resulting in false positive outcomes. Included in the Tox21 portf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…This choice relies on the evidence that many screening compounds and reference molecules interfere at UV and blue wavelengths. 30,31 In particular, we selected the NanoTemper proprietary second-generation red dye (Monolith Protein Labeling Kit RED-NHS 2nd Generation, NanoTemper Technologies) that carries a reactive NHS-ester group that reacts with primary amines of lysine residues to form a covalent bond. It is reported that the second-generation dye gives enhanced binding amplitudes and higher signal-to-noise (S/N) ratios with respect to the first-generation dye.…”
Section: Resultsmentioning
confidence: 99%
“…This choice relies on the evidence that many screening compounds and reference molecules interfere at UV and blue wavelengths. 30,31 In particular, we selected the NanoTemper proprietary second-generation red dye (Monolith Protein Labeling Kit RED-NHS 2nd Generation, NanoTemper Technologies) that carries a reactive NHS-ester group that reacts with primary amines of lysine residues to form a covalent bond. It is reported that the second-generation dye gives enhanced binding amplitudes and higher signal-to-noise (S/N) ratios with respect to the first-generation dye.…”
Section: Resultsmentioning
confidence: 99%
“…InterPred webserver (version 1.0, accessed on 3 August 2020, National Institute of Environmental Health Sciences, Durham, NC, USA) is a platform for the prediction of interference in cellular and biochemical assays that use fluorescence or luminescence as the detection technology [23]. InterPred includes 17 QSAR models that were developed using machine learning, and are based on data from more than 8,000 unique structures in assays contained in the Tox21 Consortium library, i.e., luciferase inhibition assays (tox21luc-biochem-p1), and autofluorescence assays in the HepG2 and HEK-293 cell lines, and the cell-free assay formats (tox21-spec-hepg2-p1, tox21-spec-hek293-p1, respectively) [1,23]. The intent of InterPred is to enable the identification of false-positive results due to autofluorescence and inhibition of luciferase in large high-throughput screening assays.…”
Section: In-silico Prediction With Interpredmentioning
confidence: 99%
“…Advances in high-throughput screening of compounds for biological activity have enabled the compilation of data from cell-based and biochemical assays on a myriad of biological targets for thousands of compounds, such as the US Federal Consortium on Toxicology in the 21st Century (Tox21 Consortium) program [1,2]. In this way, our knowledge of the biological activities of compounds has expanded rapidly, whereby the applicability of a compound (e.g., as a drug) and its potential toxicity can be identified early in the process of drug discovery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations